2011
DOI: 10.3126/joim.v32i3.4952
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of dysmenorrhoea associated with high stress scores among the undergraduate Nepalese medical students

Abstract: Introduction: Primary dysmenorrhoea is one of the major problems associated with menstruation among the young undergraduate medical students which affect their daily routine. Among various causes, mental stress is one of the major causes of primary dysmenorrhoea. This study aims to assess the relationship between the degree of stress and incidence of dysmenorrhoea amongst the young Nepalese medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It is clear that there are many health benefits for women who exercise regularly and in moderation. Exercise improves cardiovascular status, increased bone mineral content; improve dysmenorrhea and premenstrual syndrome symptoms 5.9,15 .Considering the side effects of drug treatments and surgery, non-drug treatments, particularly physical activity, has attracted the attention of professionals and women 8 . 6 Also, it helps in reducing pain, relieving stress, elevating mood and improving health.…”
Section: Effect Of Exercisesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear that there are many health benefits for women who exercise regularly and in moderation. Exercise improves cardiovascular status, increased bone mineral content; improve dysmenorrhea and premenstrual syndrome symptoms 5.9,15 .Considering the side effects of drug treatments and surgery, non-drug treatments, particularly physical activity, has attracted the attention of professionals and women 8 . 6 Also, it helps in reducing pain, relieving stress, elevating mood and improving health.…”
Section: Effect Of Exercisesmentioning
confidence: 99%
“…The idea that exercise might help to relieve menstrual pain is not new; in 1943 Billing proposed that women with dysmenorrhea had contracted ligamentous bands in the abdomen and subsequently developed a series of stretching exercises for which he claimed a high rate of symptom relief 7,8,15 . The belief that exercise was effective seems to have prevailed and led to anecdotal beliefs among health agencies, clinicians, and women that exercise is beneficial However, a combination of organic, psychological, and sociocultural factors may be responsible 15 .…”
Section: Effect Of Exercisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional and behavioral problems like anxiety, s t r e s s , a n d d e p r e s s i o n m a y e x a c e r b a t e dysmenorrhea. 3,11 Though dysmenorrhea is a common gynecological problem, enough hospital-based studies have not been done in Nepal to know the true extent of this problem. The aim of this study is to describe the presenting complaints in the Gynecological OPD in a tertiary hospital of Kathmandu and to describe the prevalence and assess the extent of dysmenorrhea and its impact on daily activities in the women visiting the OPD.…”
Section: Introductionmentioning
confidence: 99%
“…10 A study conducted among medical students in Nepal found the prevalence of dysmenorrhea to be 48%. 11 Dysmenorrhea is common in daughters of dysmenorrheic women. Various factors like low body mass index (BMI), smoking, early menarche, pelvic infections, psychological disturbances, genetic influence, and sexual assault have influence on the prevalence and severity of dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%